Efficacy, safety and tolerability of using abatacept for the treatment of rheumatoid arthritis - Rafael Venson; Astrid Wiens; Cassyano Januário Correr; Roberto Pontarolo (Universidade de São Paulo, 2012)
The objective is to provide an update on the clinical efficacy, safety and tolerability of the use of abatacept for treating rheumatoid arthritis. A systematic review (up to June 2011) followed by meta-analyses was performed. Randomized controlled clinical trials comparing abatacept at a dose of 10 mg/kg with a placebo, both with concomitant methotrexate, were used. Only high- or moderate-quality studies were included. The efficacy was evaluated based on changes in the ACR, DAS and HAQ; safety was assessed based on serious adverse events, serious infections, malignancies and deaths; tolerability was evaluated based on the withdrawals due to adverse events, serious adverse events and lack of efficacy. All these parameters were evaluated within one year of treatment. Nine studies met the inclusion criteria, comprising 4,219 patients. For all of the efficacy parameters, the abatacept group had better results than the placebo group, except in the case of HAQ improvement >0.3, which presented no statistically significant difference. None of the safety parameters presented a significant difference between the groups. The tolerability parameters were also similar between groups, with the exception of withdrawals due to lack of efficacy. For this criterion, the abatacept group presented favorably compared to the control group. Abatacept showed a higher efficacy compared to placebo without significant differences between the abatacept and control group in terms of safety. O objetivo foi fornecer dados atualizados sobre eficácia clínica, segurança e tolerabilidade do uso de abatacepte para o tratamento da artrite reumatoide. Realizaram-se uma revisão sistemática (com dados até junho/2011) e metanálises. Somente estudos clínicos controlados randomizados comparando o abatacepte (10 mg/kg) com placebo, ambos com uso concomitante de metotrexato, foram incluídos; todos possuíam qualidade alta ou moderada. A eficácia foi avaliada baseando-se em mudanças no ACR, DAS e HAQ; a segurança foi avaliada pelos eventos adversos e infecções graves, malignidades e mortes e a tolerabilidade pelo abandono do tratamento devido a eventos adversos (graves ou não) e falta de eficácia. Todos esses parâmetros foram avaliados ao final de um ano de tratamento. Nove estudos se adequaram aos critérios de inclusão, envolvendo 4219 pacientes. Em todos os parâmetros avaliados, o grupo tratado com abatacepte obteve melhores resultados, exceto para a melhora (>0,3) no HAQ (sem diferença estatisticamente significativa). Nenhum critério de segurança ou tolerabilidade apresentou diferença significativa entre os grupos, com exceção dos abandonos devido à falta de eficácia (grupo abatacepte apresentou resultados favoráveis em relação ao controle). O abatacepte possui maior eficácia quando comparado com o placebo, sem diferença significativa entre os grupos em termos de segurança.